2019
DOI: 10.3390/medicina55040095
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Endotyping in Chronic Rhinosinusitis—A Paradigm Shift

Abstract: Chronic rhinosinusitis (CRS) is a heterogeneous chronic inflammatory condition of the paranasal sinuses and nasal passage. It is characterized as inflammation of the sinonasal passage, presenting with two or more symptoms (nasal blockage, secretions, facial pain and headaches) for more than 12 weeks consecutively. The disease is phenotypically differentiated based on the presence of nasal polyps; CRS with nasal polyps (CRSwNP) and CRS without nasal polyps (CRSsNP). Traditionally, CRSwNP has been associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 79 publications
1
63
0
Order By: Relevance
“…Likely, the neutrophilic influx is driven by other cytokines that are known to be enhanced in CRSsNP, such as IL-6, IL-8, IL-17, and TNF-a. 4,5,8,9 Interestingly, here we have demonstrated decreased IL-17 levels in patients with CRSsNP with an underlying type 2 inflammation. This is in line with earlier reports showing that T H 17 response is suppressed in a type 2 environment in CRSwNP, which results in 2 distinctive groups of IL-5 low /IL-17 high and IL-5 high /IL-17 low patients with CRSsNP.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Likely, the neutrophilic influx is driven by other cytokines that are known to be enhanced in CRSsNP, such as IL-6, IL-8, IL-17, and TNF-a. 4,5,8,9 Interestingly, here we have demonstrated decreased IL-17 levels in patients with CRSsNP with an underlying type 2 inflammation. This is in line with earlier reports showing that T H 17 response is suppressed in a type 2 environment in CRSwNP, which results in 2 distinctive groups of IL-5 low /IL-17 high and IL-5 high /IL-17 low patients with CRSsNP.…”
Section: Discussionsupporting
confidence: 48%
“…[4][5][6] On the other hand, CRSsNP is often considered primarily as a type 1 to type 3 inflammation, which is associated with neutrophils and regulated by elevated levels of IL-6, IL-8, IL-17, and TNF-a. 5,[7][8][9] Although this dichotomous classification is still used in daily clinics, further endotyping has suggested that CRS is a more complex disease, often with mixed inflammatory patterns. 4,6,[9][10][11] Remarkably, 30% of European patients and 55% of North American patients with CRSsNP also showed a mild to moderate-and in some cases mixed-type 2 inflammation.…”
mentioning
confidence: 99%
“…Moreover, in these subjects, IL-5-dependent eosinophilia can also contribute to the development of clinically significant comorbidities such as chronic rhinosinusitis with nasal polyps. Indeed, these upper airway disorders originate from cellular and molecular mechanisms, which appear to be very similar to those underlying type 2 inflammation in asthma (Heffler et al, 2018(Heffler et al, , 2019Ahern and Cervin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, chronic rhinosinusitis is considered a multifactorial disease, linked to immunological factors, local host factors, superantigens, inflammation and associated comorbidities, such as asthma, allergic rhinitis or Samter’s triad. Based on the presence or absence of nasal polyps, two different phenotypes have been initially identified, CRS without nasal polyps (CRSsNP) and CRS with nasal polyps (CRSwNP) [ 6 ]. They have been associated with different inflammatory profiles, with CRSsNP being characterized by a neutrophilic type of inflammation, while CRSwNP was considered mainly eosinophilic.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, CRS is considered to have multiple phenotypes and endotypes, differentiated by clinical factors, immunological factors and various biomarkers [ 7 ]. Endotyping achieves the classification of CRS cases by defining inflammatory markers, clinical features, local microbiota, nasal secretions [ 6 ] and other parameters, so that a more accurate description is obtained. Identifying these factors could lead to a more precise diagnosis, identification of potentially resistant cases and designing an individualized, endotype driven treatment.…”
Section: Introductionmentioning
confidence: 99%